2018
DOI: 10.1016/j.joca.2017.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Sagittal alignment and mobility of the thoracolumbar spine are associated with radiographic progression of secondary hip osteoarthritis

Abstract: The findings suggest that spinal alignment and mobility should be considered when assessing risk and designing preventive intervention for radiographic progression of secondary hip OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 54 publications
2
36
0
Order By: Relevance
“…Changes in the postural alignment observed in hip OA are not only related to the disturbed balance of the entire body and low back pain, but may also promote hip OA progression. A prospective cohort study of patients with pre-to advanced stage hip OA reported that anterior spinal inclination excluding the pelvis was a risk factor for subsequent hip OA progression 21 ) . Spinal malalignment may cause changes in the mechanical environment of the hip joint that, in turn, may lead to OA progression.…”
Section: Postural Alignment and Hip Oa Progressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in the postural alignment observed in hip OA are not only related to the disturbed balance of the entire body and low back pain, but may also promote hip OA progression. A prospective cohort study of patients with pre-to advanced stage hip OA reported that anterior spinal inclination excluding the pelvis was a risk factor for subsequent hip OA progression 21 ) . Spinal malalignment may cause changes in the mechanical environment of the hip joint that, in turn, may lead to OA progression.…”
Section: Postural Alignment and Hip Oa Progressionmentioning
confidence: 99%
“…Spinal malalignment may cause changes in the mechanical environment of the hip joint that, in turn, may lead to OA progression. In addition, spinal dysfunction, such as decreased mobility of the thoracolumbar spine, may influence hip OA progression 21 ) . Decreased spinal mobility interferes with the aforementioned compensatory mechanisms for the disrupted balance in the standing posture.…”
Section: Postural Alignment and Hip Oa Progressionmentioning
confidence: 99%
“…Details of postural and gait assessment were described elsewhere 8,9 . Briefly, spinal alignment in the sagittal plane was measured using the Spinal Mouse a , which is a reliable and valid non-invasive device to measure spinal alignment and RoM [17][18][19] .…”
Section: Postural Assessmentmentioning
confidence: 99%
“…Patients with hip OA also show abnormalities in gait such as slow gait speed, short stride length, and decreased hip motions and hip joint moments in three dimensions 6,7 . Gait-and posture-related factors such as inclination of the spine in standing and excessive hip loading during gait have been shown to be associated with radiographic progression of hip OA 8,9 . Clinical progression is not necessarily related to the radiographic progression in OA 10 .…”
mentioning
confidence: 99%
“…Mechanical stress on the articular cartilage encourages osteoarthritis (OA) progression [ 1 3 ]. Hip OA decreases an individual’s range of motion [ 4 – 6 ], muscle strength [ 6 – 9 ], and physical functioning [ 10 ]; degrades their health-related quality of life [ 11 ]; and results in hip joint pain [ 5 , 6 , 12 , 13 ]. Therefore, the reduction in the mechanical stress on the hip articular cartilage is important in daily life to prevent OA morbidity and progression.…”
Section: Introductionmentioning
confidence: 99%